Mortality of adolescents due to self-inflicted injuries in Brazil (2004–2023): A population-based study (Research, Society and Development, 2025)
This study aims to analyze cases of mortality among adolescents due to self-inflicted injuries in Brazil, using population-based data from the Mortality Information System (SIM). This is a descriptive, retrospective, population-based study analyzing 18,058 deaths among adolescents aged 10 to 19 years. The results showed that 67.6% of deaths occurred among males, with the 15–19 age group accounting for 84.6% of cases. The most common method was hanging, strangulation, and suffocation (69% of the total), followed by the use of firearms and pesticide poisoning. The highest concentration of deaths was observed in the Southeast (28.6%) and Northeast (25.3%) regions. Additionally, 58.5% of deaths occurred at home, and most victims had between 4 and 11 years of schooling. These findings reinforce the need for public suicide prevention policies targeting the adolescent population, with emphasis on early detection of psychological distress, strengthening of support networks, and addressing social inequalities.